1988
DOI: 10.1590/s0074-02761988000200007
|View full text |Cite
|
Sign up to set email alerts
|

Colicinogeny in Salmonella serovars isolated in Brazil

Abstract: A study of colicinogeny was made in 748 strains of Salmonella (97 serovars) isolated from different sources: human (291), animal (119), environmental (141), food (102) and animal feed (95). Colicin production was detected in 64 strains (8.6%), particularly isolated from foods (30.4%). Col E1 (53) and Ia (44) were the most frequently observed, especially in S. agona for environment and food sources. Col V production was identified in 5 strains of S. typhimurium within 8 producer cultures isolated from humans. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…genomes for bacteriocin sequences that could be used by the pathogen to target host commensals during infection—we performed blast searches using E. coli colicins and microcins as query (File S1). Results confirmed the presence of ColB, ColE1, ColE2, ColIa, ColIb, ColM, and ColS4 in several S. enterica genomes (Table S1), as previously reported [148–150]. In addition, we identified ColE3‐E9, ColN, Col5, and Col10 (Table S1).…”
Section: Interbacterial Competition After the Induction Of Inflammationsupporting
confidence: 90%
See 1 more Smart Citation
“…genomes for bacteriocin sequences that could be used by the pathogen to target host commensals during infection—we performed blast searches using E. coli colicins and microcins as query (File S1). Results confirmed the presence of ColB, ColE1, ColE2, ColIa, ColIb, ColM, and ColS4 in several S. enterica genomes (Table S1), as previously reported [148–150]. In addition, we identified ColE3‐E9, ColN, Col5, and Col10 (Table S1).…”
Section: Interbacterial Competition After the Induction Of Inflammationsupporting
confidence: 90%
“…Indeed, in vitro studies showed that some S. enterica strains are susceptible to E. coli colicins such as ColB, ColIa, ColIb, ColM, ColS4, Col5, and Col10 [130,146,147] (Table S1). At the same time, some S. enterica strains also produce colicins that affect E. coli , like ColB, ColE1, ColE2, ColIa, ColIb, ColK, ColM, and ColS4 [148–150] (Table S1). In addition to colicins homologous to E. coli , five colicin‐like proteins named salmocins were detected in several S. enterica serovars [130] (Table S1).…”
Section: Interbacterial Competition After the Induction Of Inflammationmentioning
confidence: 99%